Reflections on the contribution of the geography teacher beyond formal education - de Menezes Júnior, Edmário Marques; Costa, Brenda Martoni Mansur Corrêa da; Silva, Wemerson Flávio da (Revista Ensino de Geografia (Recife), 2022)
The article aims to seek reflections on Geography as a curricular component in elementary schools and the role of the geography teacher in the contemporary context. The methodology used starts from the bibliographical research under the bias of the qualitative approach from the assumptions of the school and its objectives, the social role of the teacher, especially the geography teacher with his knowledge and the trans and multidisciplinarity of geographical science that exceeds the limits of formal education. As results/discussions, the School Geography has an essential role in Brazilian schools, for developing critical-analytical sense, responsible action in the geographic space and the exercise of citizenship. In addition, guidelines were highlighted thatcontribute to reshaping educational practices toovercome traditionalism and disciplinary and pedagogical fragmentation. In conclusion, there is a continuous need and greater investment for training qualification in school geographical teaching and new propositions in classrooms and in the teacher-student relationship that consider the balance between content, learning by doing, sharing yourself in the world and a teacher who proposes to reflect and question that student.